What is important in transdisciplinary pain neuroscience education? A qualitative study. Issue 18 (28th August 2018) - Wijma, Amarins J.; Speksnijder, Caroline M.; Crom-Ottens, Astrid F.; Knulst-Verlaan, J. M. Corine; Keizer, Doeke; Nijs, Jo; van Wilgen, C. Paul
Abstract: Purpose: The main focus of Pain Neuroscience Education is around changing patients' pain perceptions and minimizing further medical care. Even though Pain Neuroscience Education has been studied extensively, the experiences of patients regarding the Pain Neuroscience Education process remain to be explored. Therefore, the aim of this study was to explore the experiences in patients with non-specific chronic pain. Materials and methods: Fifteen patients with non-specific chronic pain from a transdisciplinary treatment centre were in-depth interviewed. Data collection and analysis were performed according to Grounded Theory. Results: Five interacting topics emerged: (1) "the pre-Pain Neuroscience Education phase", involving the primary needs to provide Pain Neuroscience Education, with subthemes containing (a) "a broad intake" and (b) "the healthcare professionals"; (2) "a comprehensible Pain Neuroscience Education" containing (a) "understandable explanation" and (b) "interaction between the physiotherapist and psychologist"; (3) "outcomes of Pain Neuroscience Education" including (a) "awareness", b) "finding peace of mind", and (c) "fewer symptoms"; 4) ""scepticism" containing (a) "doubt towards the diagnosis and Pain Neuroscience Education", (b) "disagreement with the diagnosis and Pain Neuroscience Education", and (c) "Pain Neuroscience Education can be confronting". Conclusion: This is the first study providing insight into the constructs contributing to the Pain Neuroscience Education experience of patients with non-specific chronic pain. The results reveal the importance of the therapeutic alliance between the patient and caregiver, taking time, listening, providing a clear explanation, and the possible outcomes when doing so. The findings from this study can be used to facilitate healthcare professionals in providing Pain Neuroscience Education to patients with non-specific chronic pain. Implications for Rehabilitation: An extensive biopsychosocial patient centred intake is crucial prior to providing Pain Neuroscience Education. Repetitions of Pain Neuroscience Education, in different forms (verbal and written information, examples, drawings, etc.) help patients to understand the theory of neurophysiology. Pain Neuroscience Education induces insight into the patient's complaints, improved coping with complaints, improved self-control, and induces in some cases peace of mind. Healthcare professionals providing Pain Neuroscience Education should be aware of the possible confronting nature of the contributing factors.